Colonial taxation in Africa. A fiscal history of the Congo through the lens of customs (1886-1914) - De Roo, Bas (Afrika Focus, 2018)
Every colonial state in Africa faced the fiscal challenge of ruling vast, inaccessible and thinly populated territories that produced relatively little taxable wealth, without metropolitan grants-in-aid and with limited access to international bond markets. How colonial states dealt with this challenge determined how much resources could be invested in the administration of African colonies and how the colonizer interacted with the colonized. As such, taxation fundamentally shaped colonial rule. Thus far, most scholars have either studied the practice of “native” taxation or the general spending and revenue-raising patterns of colonial administrations. This thesis shines a new light on the fiscal history of colonial Africa – as well as the colonial history of the Congo – by focusing on customs, the second fiscal pillar on which African colonial states were founded. Key words : colonial history, fiscal history, Congo Free State, Belgian Congo